Analysis and avoidance method of 5G atmospheric duct interference - Tinglan WANG; Xingzheng LI; Yimin ZUO; Dongchen ZHANG (Dianxin kexue, 2022)
Atmospheric duct effects can produce the remote interference, which will lead to serious problems of the network degradation.Firstly, a detailed analysis of the causes of 5G atmospheric duct interference was achieved through the system principle analysis.Then, a 5G atmospheric duct interference waveform identification algorithm was proposed.Finally, from the aspects of time domain, frequency, air domain, parameter configuration, etc., the avoidance and adjustment method of atmospheric duct interfered cells was proposed.The impact of the atmospheric duct interference is reduced and the quality of 5G networks is ensures.